1991
DOI: 10.1111/j.1570-7458.1991.tb01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding site selection of first‐instar larvae of Cnaphalocrocis medinalis on susceptible and resistant rice plants

Abstract: More first‐instar larvae of the rice leaffolder, Cnaphalocrocis medinalis (Guenée), were recovered from susceptible IR36 and Roxoro rice varieties than resistant TKM6 and Oryza perennis, 24 h after infestation. Within a rice plant, a higher proportion of larvae was recovered from young whorl leaf, followed by mature leaves and leafsheaths on all the four rice varieties tested. However, differences were observed between susceptible and resistant varieties in the distribution of larvae on these three plant parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Resistance to the southwestern corn borer Diatraea grandiosella (Dyar) and European corn borer Ostrinia nubilalis (Hubner) (Lepidoptera: Pyralidae) in resistant corn hybrids is greater in the vegetative than the reproductive stages (Klun & Robinson, 1969; Videla et al , 1992). Conversely, resistance to the rice leaffolder Cnaphalocrocis medinalis (Guené) (Lepidoptera: Pyralidae) is more pronounced in older foliage of resistant varieties than in young foliage (Ramanchandran & Khan, 1991). Therefore, the study of parameters, such as plant age and number of insects, is necessary in the study of plant resistance to insects.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to the southwestern corn borer Diatraea grandiosella (Dyar) and European corn borer Ostrinia nubilalis (Hubner) (Lepidoptera: Pyralidae) in resistant corn hybrids is greater in the vegetative than the reproductive stages (Klun & Robinson, 1969; Videla et al , 1992). Conversely, resistance to the rice leaffolder Cnaphalocrocis medinalis (Guené) (Lepidoptera: Pyralidae) is more pronounced in older foliage of resistant varieties than in young foliage (Ramanchandran & Khan, 1991). Therefore, the study of parameters, such as plant age and number of insects, is necessary in the study of plant resistance to insects.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer neonate larvae preferred to settle on moderately resistant MSM lines (MSM 139 and MSM 127) than on the susceptible lines (MSM 37 and MSM 26). Earlier studies also reported a strong non-preference for larval settling and feeding on resistant wild rice species than on susceptible varieties (Medina & Tryon, 1986;Khan et al, 1989;Ramachandran & Khan, 1991). Leaf folder larvae took more time for leaf selection, making a primary fold along with more head swings in moderately resistant MSM 139 than in the susceptible MSM 37.…”
Section: Discussionmentioning
confidence: 91%
“…Tolerance is the ability of the host plant to grow and yield despite the pest attack. In the case of the rice leaf folder, both antixenosis and antibiosis mechanisms of resistance were reported (Khan et al, 1989;Ramachandran & Khan, 1991;Dakshayani et al, 1993;Xu et al, 2010;Punithavalli et al, 2014). Varying effects on leaf folding behavior by the larvae was observed in different genotypes by Punithavalli et al (2013).…”
Section: Introductionmentioning
confidence: 99%